2021
DOI: 10.36418/jist.v2i9.227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Model CIPP Program Generasi Berencana Di Dki Jakarta

Abstract: Tulisan ini berfokus pada evaluasi program Generasi Berencana (GenRe Ceria), khususnya pada akses kesehatan reproduksi, yang dilaksanakan oleh Badan Kependudukan dan Keluarga Berencana Nasional Provinsi DKI Jakarta yang menyasar pada anak perempuan sebagai subjek kebijakan. Data BKKBN menyebut 57.688.472 jiwa yang berada dalam rentang usia remaja, artinya satu dari setiap 4 orang penduduk Indonesia adalah remaja. Jumlah yang sangat besar tersebut adalah potensi yang memerlukan pengelolaan yang terencana, siste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A recent study indicated that peer educators trained within programs such as the Adolescent Friendly Center Smoking Quit Program improve students’ cognitive and behavioral change processes to quit smoking (Orsal & Ergun, 2021 ). As a peer education strategy, GenRe ambassadors focus on encouraging adolescents to postpone early marriage and prioritize school and work to create a bright future while comprehensively providing reproductive health information to prevent HIV/AIDS (Akuiyibo et al, 2021 ; Benton et al, 2020 ; Sari et al, 2021 ). Peer education, leadership characteristics, and role models make health programs preferable for students.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that peer educators trained within programs such as the Adolescent Friendly Center Smoking Quit Program improve students’ cognitive and behavioral change processes to quit smoking (Orsal & Ergun, 2021 ). As a peer education strategy, GenRe ambassadors focus on encouraging adolescents to postpone early marriage and prioritize school and work to create a bright future while comprehensively providing reproductive health information to prevent HIV/AIDS (Akuiyibo et al, 2021 ; Benton et al, 2020 ; Sari et al, 2021 ). Peer education, leadership characteristics, and role models make health programs preferable for students.…”
Section: Discussionmentioning
confidence: 99%